2018
DOI: 10.1038/s41593-018-0205-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and morphophysiological evidence for a specialized human cortical GABAergic cell type

Abstract: We describe convergent evidence from transcriptomics, morphology and physiology for a specialized GABAergic neuron subtype in human cortex. Using unbiased single nucleus RNA sequencing, we identify ten GABAergic interneuron subtypes with combinatorial gene signatures in human cortical layer 1 and characterize a novel group of human interneurons with anatomical features never described in rodents having large, “rosehip”-like axonal boutons and compact arborization. These rosehip cells show an immunohistochemica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
276
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(301 citation statements)
references
References 68 publications
(112 reference statements)
22
276
1
2
Order By: Relevance
“…However, among various cellular features characterized in humans but not in rodent neocortex (Blazquez-Llorca L et al 2010;Testa-Silva G et al 2010;Molnar G et al 2016;Szegedi V et al 2016;Wang B et al 2016;Beaulieu-Laroche L et al 2018;Boldog E et al 2018;Goriounova NA et al 2018;Kalmbach BE et al 2018;Pruunsild P and H Bading 2019), human neocortical neurons exhibit higher Rm than their rodent counterparts do (Eyal G et al 2016;Poorthuis RB et al 2018). Although our data here showed that human and mouse pvBC input resistance values were not different on average (showing p value of 0.10), human neurons had individual cells showing clearly higher Rm than did those found in any of the mouse pvBCs (Poorthuis RB et al 2018).…”
Section: Pvbc Features In Humans and Micecontrasting
confidence: 64%
“…However, among various cellular features characterized in humans but not in rodent neocortex (Blazquez-Llorca L et al 2010;Testa-Silva G et al 2010;Molnar G et al 2016;Szegedi V et al 2016;Wang B et al 2016;Beaulieu-Laroche L et al 2018;Boldog E et al 2018;Goriounova NA et al 2018;Kalmbach BE et al 2018;Pruunsild P and H Bading 2019), human neocortical neurons exhibit higher Rm than their rodent counterparts do (Eyal G et al 2016;Poorthuis RB et al 2018). Although our data here showed that human and mouse pvBC input resistance values were not different on average (showing p value of 0.10), human neurons had individual cells showing clearly higher Rm than did those found in any of the mouse pvBCs (Poorthuis RB et al 2018).…”
Section: Pvbc Features In Humans and Micecontrasting
confidence: 64%
“…A notable limitation of our DE analysis was the sample size of our dataset (7 donors). A small sample size in a single cell genomics study does affect statistical power, but does not preclude the possibility of drawing meaningful inferences of cell type gene expression in the human brain (9,41) . That said, our goal is to increase the sample size for future single cell studies to better identify important expression patterns, particularly for genes that have smaller effect sizes.…”
Section: Differential Expression and Pathway Analysismentioning
confidence: 99%
“…While we utilized RNAscope technology for fluorescent probe labeling, non-commercial smFISH technologies have also proven successful in postmortem human brain tissue 4 . However, RNAscope offers a rapid, robust, and universal approach that has now been replicated by several groups for qualitative validation of RNA-seq data in postmortem human brain tissue [3][4][5]18 .…”
Section: Dodotdot Overcomes Tissue Autofluorescence To Accurately Promentioning
confidence: 99%
“…The widespread generation of single-cell RNA-seq data sets in the neurosciences has fueled a resurgence of smFISH approaches to validate cell type-specific molecular profiles by visualizing individual transcripts at cellular resolution 3,4 . Information from single-cell RNA-seq data has revealed increasingly complex transcriptomic signatures for functionally distinct cell types, including the recently identified Rosehip neurons in cortical layer one 5 and cells with neurogenic potential in the dentate gyrus of the hippocampus 6,7 , such that molecular definition of these cells necessitates combinatorial labeling with multiple probes to confirm both presence and absence of specific transcripts within a spatially-defined context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation